The Supply Chain Structure of Toys and Its Impact on Children’s Development and Innovation - Parvin Shokri (International Journal of Supply Chain Management, 2018)
Kids creativity grows with playing various games and empowering this creativity not only leads them to have a better educational path, but also provides a suitable platform for their social growth, skill development and innovation. Toys are usually the basic parts of the games and have a big contribution on childrens progress. Analyzing the supply chain structure of toys and its impact on childrens development is the subject of this study. Observing the reaction of school-aged children while facing the moving elements of a picture was a part of this research. The results indicate that the supply chain structure of a toy has a strong power to attract childrens attention and as a result can easily help them to explore the world they live in.